Efforts to Eradicate Land Mafia in Banjarbaru City - Tumanggor, Evans Ricardo; Sri Darmadi, Nanang; Tri Bawono, Bambang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
Land mafia is a serious problem that can be detrimental to society and the state. As a serious problem, the law, which is a state instrument in national land management and is mandated to eradicate land mafia, has not been optimally implemented. This is evidenced by the increasing number of land mafia cases, including in the Banjarbaru City area. The type of legal research used is non-doctrinal. In this non-doctrinal legal research, law is conceptualized as a manifestation of the symbolic meanings of social actors as seen in their interactions. That the real reality of life does not exist in the empirical realm that is also the realm of observation, it does not appear in the form of patterned and structured behavior that is objective (let alone normative) and therefore can be measured to produce quantitative data. Based on the research conducted, it was found that the implementation of efforts to eradicate land mafia in the Banjarbaru City area is currently not optimal, this is becauseThe absence of regulations regarding the criminal law enforcement process in the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning the Prevention and Eradication of Land Mafia. Therefore, the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning the Prevention and Eradication of Land Mafia only regulate the implementation of handling land mafia cases with an administrative approach, this results in a lack of severe sanctions to create a deterrent effect for land mafia perpetrators inBanjarbaru City.